EFEKTIVITAS PENGGUNAAN THERMOSTATIC EXPANTION VALVE PADA REFRIGERASI AC SPLIT - Harianto -; Eka Yawara (Universitas Muhammadiyah Semarang, 2013)
Vapor compression refrigeration is one of refrigeration systems that is mostwidely used for the cooling process in a variety of human needs. In this type of machine there is a component that can be varied kind, namely the expansion valve, such as a capillary tube and thermostatic expansion valve (TXV).Experimental tests have been conducted in a one HP split air conditioningrefrigeration machine capacity to compare the performances between the useof a capillary tube and TXV expansion valve. The experimental results showthat the use of a capillary tube responds to the greater cooling load of thesmaller COP, COP highest achieved in the condition of the refrigerant out ofthe evaporator in the form of vapor saturated with COP = 5.3. While the useof TXV, COP value increases with the addition of the cooling load. Thehighest COP achieved is 5.87.